2020
DOI: 10.1016/j.esxm.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Surgical Technique for Reservoir Placement During Inflatable Penile Prosthesis Implantation

Abstract: Introduction At the moment, there is an ongoing debate regarding the controversial issue of the ideal reservoir placement (RP) surgical technique during implantation of a 3-piece inflatable penile prosthesis, but a definitive winner has not yet emerged. Aim In this light, we herein describe our modified technique for RP into the space of Retzius through the external oblique muscle fascia and present its results. Methods In total, 253 inflatab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This is an easily reproducible technique as the fascia can be visualized medially by lateral retraction of the spermatic cord and punctured with Metzenbaum scissors. 15 This technique depends on access to the SOR which might be violated in patients after radical prostatectomy or cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is an easily reproducible technique as the fascia can be visualized medially by lateral retraction of the spermatic cord and punctured with Metzenbaum scissors. 15 This technique depends on access to the SOR which might be violated in patients after radical prostatectomy or cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have presented different approaches (penoscrotal, infrapubic, or subcoronal) regarding accessing the corporal bodies during IPP surgery [13][14][15]. Moreover, the serious reservoir placement-related complications and increased application of surgical approaches, which compromise the space of Retzius, led prosthetic urologists to introduce innovative Retzius sparing reservoir placement techniques [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RTEs were developed in 1981 and quickly became popular among implanters as a measure to minimize friction of the tubing against the cylinder wall. The reported high RTE use rate, from 58% up to 73%, during IPP surgeries suggests that this innovation gave surgeons flexibility 13.5 (12)(13)(14)(15) in placement of corporotomies and minimization of intracorporeal tubing [16]. However, it has separately reported that RTE utilization be kept to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Placement in this space avoids intra-abdominal complications and allows a low-pressure space for the reservoir ( 40 ). Access could be obtained through a separate suprapubic incision or in the same—e.g., in the penoscrotal approach—incision via the inguinal canal or the external oblique muscle fascia ( 41 ). The fascia transversalis could be perforated with the finger, sharp or with a nasal speculum ( 42 - 44 ).…”
Section: Previous Pelvic Surgerymentioning
confidence: 99%
“…Due to previous surgery—such as radical prostatectomy, radical cystectomy or colorectal surgery—the Retzius space could be compromised which could result in a higher risk of complication, e.g., damage to iliac vessels, bladder or intestines ( 41 ).…”
Section: Previous Pelvic Surgerymentioning
confidence: 99%